Fibrinolysis and aspiration of experimental intracerebral hematoma reduces the volume of ischemic brain in rats - Deinsberger, Wolfgang; Vogel, Johannes; Fuchs, Casten; Michael Aueri, Ludwig; Kuschinsky, Wolfgang; Böker, Dieter Karsten (Neurological research, 1999)
The hypothesis was tested in rats that brain ischemia by an intracerebral hematoma can be ameliorated by fibrinolysis and aspiration of the hematoma. Intraparenchymal blood clots were generated by the injection of 50μI of autologous blood into the right caudate nucleus in two portions seven minutes apart. Thirty or 120 min later 12 fil recombinant tissue plasminogen activator (rtPA) or 0.9% NaCI were injected and after 30 min the resolved hematoma was aspirated. Six hours later cerebral blood flow (CBF) was determined by 14C-iodoantipyrine autoradiography. Tissue volumes of CBF < 10 ml 1 00 g-1 min-1 and CBF < 30 ml g"1 min’1 were determined. Clot and lesion volume were quantified histologically from serial sections stained for succinate-dehydrogenase (SDH) activity. In rtPA-treated rats the major part of the hematoma could be evacuated 30 min as well as 120 min after production of the clot. The volume of ischemic brain (CBF < 10) was significantly reduced fp<0.05) in the rtPA group compared to saline- treated and control groups irrespective of the time of treatment. In contrast, no difference was found between the control group and the experimental groups when the volumes of brain tissue surrounding the lesion were compared which had values of CBF<30 ml lOOgmin-1. In a rat model of intracerebral hemorrhage, treatment by local fibrinolysis followed by aspiration of the hematoma is effective in reducing the volume of ischemic brain tissue and of the remaining clot volume. [Neurol Res 1999; 21: 517-523]